Behavior of two peach cultivars with 'Januária' as a Japanese plum interstock - Filho, João Aleixo Scarpare; Kluge, Ricardo Alfredo; Filho, Ricardo Victoria; Neto, João Tessarioli; Jacomino, Angelo Pedro (Pesquisa Agropecuaria Brasileira, 2000)
The effects of interstock with 'Januária' Japanese plum (Prunus salicina L.) were verified in the performance of peach (Prunus persica L.) cultivars Tropical and Ouromel-2. The basic rootstock used was 'Okinawa' peach. Two crops were evaluated at fourth and fifth leaves of plants established in 1994. The interstock caused decrease of the vigour of the plants _ perimeter and cross-sectional area of the trunk, perimeter of the primary branches and length of the internodes _ and increased fruit weight and production per plant, in comparison to the plant control without interstock budded on 'Okinawa'. Yield efficiency, fertility index, flowering and fruit set were increased with 'Januária' interstock. This interstock process presents an adequate characteristic of compatibility for the peach tree, as a form of compacting the plants, increasing the productivity and the fruit size.